2008
DOI: 10.1021/jo800617y
|View full text |Cite
|
Sign up to set email alerts
|

Regioselectivity in the Ligand-Assisted Addition of Vinylmagnesium Bromide: An Experimental and Theoretical Study on the γ-Alkoxycyclobutenone Model

Abstract: Compounds 2 (M = Mg) obtained in the mono addition of vinylmagnesium bromide to squarates are attractive structural models to determine the influence of complexation between magnesium(II) and the alkoxide group on the regioselectivity of the 1,2- versus 1,4-addition of organomagnesium by complex induced proximity effects (CIPE). The 1,4-addition is observed almost exclusively in the case of vinylmagnesium in THF solution with formation of hydroxyketones type 5, which are always side or minor products in the kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…These studies are challenging because numerous nucleophilic species could be present: those species could be neutral or charged, they could be monomers or dimers, and they could involve one or more molecules of solvent. 117 Furthermore, difficulties associated with delocalized charges in intermediates requires examining them at relatively high levels of theory, taking into account electronelectron interactions. 118 Many of these issues have been addressed for reactions of carbonyl compounds with MeMgCl.…”
Section: Computational Studies Of Mechanismmentioning
confidence: 99%
“…These studies are challenging because numerous nucleophilic species could be present: those species could be neutral or charged, they could be monomers or dimers, and they could involve one or more molecules of solvent. 117 Furthermore, difficulties associated with delocalized charges in intermediates requires examining them at relatively high levels of theory, taking into account electronelectron interactions. 118 Many of these issues have been addressed for reactions of carbonyl compounds with MeMgCl.…”
Section: Computational Studies Of Mechanismmentioning
confidence: 99%
“…In addition to the MP2 study mentioned (vide supra), [20] the generalized gradient-corrected PBE functional was used to determine the mechanism of allyl isomerization as catalyzed by organomagnesium clusters, [21] and the B3LYP/6-31G* level of theory was employed to explain the regioselectivity of the reaction between vinylmagnesium bromide and γ-alkoxycyclobutenones. [22] The structure of phenylmagnesium hydride [5] has been determined at the B3LYP/6-31+G** level of theory, while the binding of the magnesium cation to benzene was studied using the MPW1PW91 functional. [10c] A report of the application of ab initio, density functional, and high level composite wave function theory calculations [23] to an investigation of the kinetic basicity of the organometallic molecules [HCCLiCl] − and [HCCMgCl 2 ] − when these anions were complexed to either LiCl or MgCl 2 in the gas phase can also be noted.…”
Section: Of 11 | Tabares and Zoellnermentioning
confidence: 99%
“…Although reports of computational studies of organomagnesium compounds are relatively rare, some investigations have been reported. In addition to the MP2 study mentioned (vide supra), the generalized gradient‐corrected PBE functional was used to determine the mechanism of allyl isomerization as catalyzed by organomagnesium clusters, and the B3LYP/6‐31G* level of theory was employed to explain the regioselectivity of the reaction between vinylmagnesium bromide and γ‐alkoxycyclobutenones . The structure of phenylmagnesium hydride has been determined at the B3LYP/6‐31+G** level of theory, while the binding of the magnesium cation to benzene was studied using the MPW1PW91 functional.…”
Section: Introductionmentioning
confidence: 99%
“…[2d], [2e], [2f], [2g], In addition, Grignard species in solution are described by the Schlenk equilibrium, which depends on the nature of the halogen (X) and alkyl (R) group, concentration, temperature, and solvent used. [2a], Grignard reagents are also known to form aggregates in ether solvent and the degree of aggregation depends on the above‐mentioned parameters , . A recent theoretical study showed that the solvent dynamics are key to the Schlenk equilibrium …”
Section: Introductionmentioning
confidence: 99%